An initial exploration of the perceptions of preparedness to practise among Saudi Arabian trained hospital pharmacists - Ameer, Luma (Pharm Pract (Granada), 2018)
BACKGROUND: There is a dearth of literature on perceptions of preparedness to practise, which explores the extent to which educational institutions prepare their students to fulfil their professional role. OBJECTIVE: The aim of this study was to explore perceptions of preparedness to practise among Saudi Arabian pharmacy graduates working in hospital. METHOD: Face-to-face, semi-structured interviews were conducted with ten hospital pharmacists based in four hospitals in the Eastern Province of Saudi Arabia who had qualified within the last five years from a Saudi Arabian School of Pharmacy. Interviews focused on expectations of hospital practise, perceptions of preparedness and challenges encountered, and reflections on how to better prepare students. Interviews were audio-recorded, transcribed and analysed thematically by two independent researchers using the Framework Approach. RESULTS:: Five key themes were identified: expectations versus reality of practise; issues relating to university course; practice related training; adapting to the work environment; and proposed improvements to undergraduate education. Participants were generally disappointed to find practise was not as expected. University training was largely didactic, with skills such as critical thinking not being sufficiently developed. Where practice related training was provided, it was variable in length and content. Cultural issues, most notably working in a mixed sex environment, were also considered to impact preparedness. Suggested improvements included greater focus on skills development and structured training placements. CONCLUSIONS: Participants experiences in university, and experiential placements varied greatly and were perceived to impact greatly on preparedness to practise. Further multiple perspective exploration of perceptions of preparedness to practise is warranted.